VALIDITAS DAN RELIABILITAS INSTRUMEN GABUNGAN MODEL EVALUASI SISTEM INFORMASI GIZI TERPADU - Diwian Jaya Putra, I Putu Okta; Purnami, Cahya Tri; Kartini, Apoina (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
Information systems that have been used for a long time should receive an evaluation of their use, one of which is SISFO Gizi Terpadu e-PPGBM. To evaluate an information system, several evaluation models can be used which have their focus on evaluation. Because these evaluation models have their focus, this research tries to combine a few evaluation models that will later be used to evaluate the e-PPGBM Integrated Nutrition SISFO. Before being used for evaluation, the newly formed combined information system evaluation model must first pass validity and reliability tests. Testing was carried out on 89 e-PPGBM users in Bali Province in a cross-sectional manner. Based on convergent validity, discriminant validity, and composite reliability testing, which was carried out using SmartPLS 4, it was found that all indicators in the e-PPGBM Integrated Nutrition SISFO evaluation model were declared valid and reliable. Structural model testing was also carried out and obtained an R-square value for the intention variable to use e-PPGBM of 0.627. This means that the influence of technology, human, and social influence variables on the intention to use the e-PPGBM variable is 62,7%, while other factors influenced the 36.9% remaining of it. Also, using e-PPGBM is only 4,1% influenced by the variable intention to use e-PPGBM. So, it can be interpreted that many other factors that are thought to influence the use of e-PPGBM.